WAYS TO IMPROVE THE EFFECTIVENESS OF GENERAL PHYSICAL TRAINING TOOLS FOR SCHOOL-AGE BASKETBALL PLAYERS (World Bulletin of Physical Education and Sports Science, 2026)
Achieving high results in modern sports depends on the systematic results of long-term training. The athlete's attitude to the training process and his sporting duty largely stems from his training motivation and participation in competitions.
Keywords: Psychology, sports, basketball, physical education, preparation, competition, training, coach, victory, sports psychology.